(untitled) (International Current Pharmaceutical Journal, 2014)
Dexamethasone is a type of steroid medication having anti-inflammatory and immunosuppressant effects. One of the major problems with this drug is its low solubility in water which results into poor bioavailability after oral administration. So the objective of the present work is to improve the solubility and dissolution rate of dexamethasone using its solid lipid nano particles (SLNPs) with stearic acid as solid lipid, lutrol F-68 as surfactant and tween-80 as stabilizer. SLNPs are prepared by hot homogenization method at different ratio of drug, lipid, surfactant and stabilizer and designated as DNP1 to DNP6. In vitro dissolution study was performed using the USP type II apparatus (paddle method) at 50 rpm to a temperature of 37°±0.5°C in distilled water containing 0.75% w/v SLS (sodium lauryl sulfate). The absorbance of sample was measured spectrophotometrically at ?max 239nm on a UV-Visible spectrophotometer. Release pattern of drug was found to follow zero order, first order and Korsmeyer-Peppas equations. Improvement of dissolution was observed in all the solid lipid nano particles as compared to pure drug. Pure drug showed only 27.25% release in 50 min whereas the dexamethasone SLNPs showed faster (66.19%) in vitro drug release. Hence, this finding indicates that dexamethasone SLNPs prepared by hot homogenization method can be used to enhance the dissolution rate and to show novel application to this drug delivery system. DOI: http://dx.doi.org/10.3329/icpj.v3i12.20829 International Current Pharmaceutical Journal, November 2014, 3(12): 331-335